2020
DOI: 10.1101/2020.06.22.165217
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Puromycin reactivity does not accurately localize translation at the subcellular level

Abstract: Puromycin is a tyrosyl-tRNA mimic that blocks translation by labeling and releasing elongating polypeptide chains from translating ribosomes. Puromycin has been used in molecular biology research for decades as a translation inhibitor. The development of puromycin antibodies and derivatized puromycin analogs has enabled the quantification of active translation in bulk and single-cell assays. More recently, in vivo puromycylation assays have become popular tools for localizing translating ribosomes in cells. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
1
9
1
Order By: Relevance
“…The puromycin ring during mitosis was also observed in different cell types, including CHO, Retinal Pigmented Epithelial (RPE) cells, NeuroEpithelium Stem cells (NES) (Fig. S3B), We confirmed that this translation signal was indeed active using OPP-ClickIT and HPG-ClickIT (77). We observed that the HPG-ClickIT signal gave a hazy disk in the MB in early G1(Fig.…”
Section: Midbodies and Midbody Remnants Are Sites Of Localized Transl...supporting
confidence: 66%
See 1 more Smart Citation
“…The puromycin ring during mitosis was also observed in different cell types, including CHO, Retinal Pigmented Epithelial (RPE) cells, NeuroEpithelium Stem cells (NES) (Fig. S3B), We confirmed that this translation signal was indeed active using OPP-ClickIT and HPG-ClickIT (77). We observed that the HPG-ClickIT signal gave a hazy disk in the MB in early G1(Fig.…”
Section: Midbodies and Midbody Remnants Are Sites Of Localized Transl...supporting
confidence: 66%
“…To determine whether MB mRNAs are translationally activated or silenced, we used two methods to quantify translation. We used the puromycin-based SUnSET technique to label nascent peptides and visualize sites of recent translation using anti-puromycin antibodies( 77 , 78 ), and OPP-ClickIT and HPG-ClickIT( 77 ), to determine whether active translation occurs in the MB and MBRs. Synchronized HeLa cells pulsed with puromycin for 4 minutes in early telophase (ET) showed little evidence of MB translation(~39% had rings at the ET stage)(Fig.3A, S3A).…”
Section: Resultsmentioning
confidence: 99%
“…Treating the cells with puromycin in a com bination with cycloheximide leads to the accumulation of ribosomes exclusively on start codons, which facilitates their identification by ribosome profiling [127]. On the other hand, the combined effect of puromycin and other antibiotics depends on the ratio and concentrations of these compounds and cannot always be predicted, which may lead to artifacts [128,129]. The activity of puromycin is unique; for example, structurally similar antibiotic A201A (see above) does not act as a peptide bond accep tor and only inhibits the peptidyl transferase reac tion [13,40].…”
Section: Inhibitors Of Eukaryotic Ribosomementioning
confidence: 99%
“…The RPM method takes advantage of the conjugation of puromycin to the nascent polypeptide when it terminates translation by imaging the IF signal from the resulting puromycin-conjugated nascent polypeptides as markers in situ for locations of translation in vivo ( 12 ). Routing of the puromycin-conjugated nascent polypeptides from sites of their synthesis, a concern when live cells are treated prior to fixation and IF-staining ( 20 ), is unlikely because we treated isolated chloroplasts with puromycin.…”
Section: Resultsmentioning
confidence: 99%